2010
DOI: 10.2176/nmc.50.367
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Key Hole Craniotomy for the Evacuation of Spontaneous Cerebellar Hemorrhage

Abstract: The efficacy and safety of cerebellar hemorrhage evacuation by key hole craniotomy and the importance of thorough evacuation and irrigation of the hematoma in the fourth ventricle to resolve obstructive hydrocephalus were assessed in 23 patients with spontaneous cerebellar hemorrhage (SCH) greater than 3 cm or with brainstem compression and hydrocephalus. A 5-cm elongated S-shaped scalp incision was made, and a 3-cm key hole craniotomy was performed over a cerebellar convexity area. The hematoma was immediatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Of these 121 articles, 41 (34%) articles fulfilled the predefined inclusion criteria and were therefore included in this systematic review (figure 1). 4 12–51 The 41 eligible studies described 2062 patients (40% female) of which 1171 (57%) underwent haematoma evacuation and 891 (43%) did not. Thirty-seven (90%) studies had a retrospective design.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these 121 articles, 41 (34%) articles fulfilled the predefined inclusion criteria and were therefore included in this systematic review (figure 1). 4 12–51 The 41 eligible studies described 2062 patients (40% female) of which 1171 (57%) underwent haematoma evacuation and 891 (43%) did not. Thirty-seven (90%) studies had a retrospective design.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the available literature and its limitations as described previously, there is currently insufficient published evidence to guide treatment decisions on when and for whom haematoma evacuation for spontaneous cerebellar ICH should be performed 13–51. Ultimately, randomised clinical trials may well be needed to assess the role of haematoma evacuation in patients with spontaneous cerebellar ICH.…”
Section: Discussionmentioning
confidence: 99%
“…In this technique, we performed a retrosigmoid craniotomy to gain direct access to the hematoma location. The retrosigmoid craniotomy is also known as "the keyhole craniotomy" because it is a minimally invasive approach that provides safe and easy access to the brainstem and cerebellum [ 12 ]. In this case, we performed a retrosigmoid craniectomy in order to compensate for any potential secondary swelling that may occur.…”
Section: Discussionmentioning
confidence: 99%
“…5,27 Previous studies have reported success and favorable patient outcome with MIS keyhole craniotomy for evacuation of cerebellar ICH. 28,29 An early study of endoscopic cerebellar hemorrhage evacuation showed superiority over evacuation through suboccipital craniectomy, with significantly shorter procedure times and decreased need for shunt placement. 30 More recent studies have also found surgical advantages to the endoscopic technique for cerebellar ICH evacuation, including for patients with severe fourth ventricle compression.…”
Section: Adjunctive Aspiration Devicesmentioning
confidence: 99%